LEARNING ENVIRONMENT AND STUDENT LEARNING OUTCOMES: THE ROLE OF LEARNING MOTIVATION MEDIATION (CORRELATIONAL STUDY IN GRADE XI OF SMAN 1 KADUGEDE) - Jingga Radesa; Agie Hanggara; Cucu Suhartini (Institut Pendidikan Indonesia, 2026)
This study is motivated by the relatively low learning outcomes of Grade XI students at SMAN 1 Kadugede. In the context of modern education, increasing attention has been given to the quality of the learning environment and learning motivation, as they are considered fundamental factors that directly and indirectly influence students’ learning outcomes. This study aims to analyze the effect of the learning environment on learning outcomes with learning motivation as a mediating variable. The method used in this research is a quantitative descriptive approach with a survey design. The sample consists of 192 Grade XI students at SMAN 1 Kadugede. Data were collected through questionnaires and analyzed using mediator models with the assistance of SPSS version 25 for Windows. The results show that the learning environment has a significant effect on learning outcomes, and learning motivation mediates the relationship between the learning environment and learning outcomes. These findings indicate that improving the learning environment not only has a direct impact on students’ learning outcomes but also enhances learning motivation, which in turn contributes to better learning outcomes. Therefore, strengthening both the learning environment and learning motivation is essential for improving students’ academic performance.